Keratin 17 Suppresses Cell Proliferation and Epithelial-Mesenchymal Transition in Pancreatic Cancer - Zeng, Yong; Zou, Min; Liu, Yan; Que, Keting; Wang, Yunbing; Liu, Changan; Gong, Jianpin; You, Yu (Frontiers in Medicine, 2020)
Keratin 17 (K17), a member of type I acidic epithelial keratin family, has been reported to be upregulated in many malignant tumors and to be involved in promoting the development of tumors. However, the precise role of K17 in progression of pancreatic cancer is still unknown. In this study, we found that K17 expression was highly expressed in pancreatic cancer tissues and cell lines and that upregulated expression was associated with the pathological grade and poor prognosis. K17 expression served as an independent predictor of pancreatic cancer survival. Meanwhile, we showed that knocking down K17 induced pancreatic cancer cell proliferation, colony formation and tumor growth in xenografts in mice. However, K17 upregulation inhibited pancreatic cancer cell proliferation and colony formation. Further mechanistic study revealed that K17 knockdown promoted cell cycle progression by upregulating CyclinD1 expression and repressed cell apoptosis. However, K17 upregulation suppressed cell cycle progression by decreasing CyclinD1 expression, and it induced apoptosis by increasing the levels of cleaved Caspase3. In addition, K17 knockdown promoted pancreatic cancer cell migration and invasion, but K17 upregulation suppressed cell migration and invasion. Moreover, knocking down K17 promoted epithelial-mesenchymal transition (EMT) in pancreatic cancer cell by inhibiting E-cadherin expression and inducing Vimentin expression, and the effects of K17 upregulation were opposite to that of K17downregulation. Taken together, our findings suggest that K17 functions as a potential tumor suppressor, even though it is upregulated in pancreatic cancer.